Changes in Physical Fitness After 12 Weeks of Structured Concurrent Exercise Training, High Intensity Interval Training, or Whole-Body Electromyostimulation Training in Sedentary Middle-Aged Adults: A Randomized Controlled Trial - Amaro-Gahete, Francisco J.; De-la-O, Alejandro; Jurado-Fasoli, Lucas; Dote-Montero, Manuel; Gutiérrez, Ángel; Ruiz, Jonatan R.; Castillo, Manuel J. (Frontiers in Physiology, 2019)
This study aimed to investigate the influence of different exercise training modalities ([i] a concurrent training based on physical activity recommendation from the World Health Organization group (PAR group), [ii] a high intensity interval training group (HIIT group), and [iii] a high intensity interval training adding whole-body electromyostimulation group (WB-EMS group)) on physical fitness in sedentary middle-aged adults. A total of 89 (52.7% women) middle-aged sedentary adults (53.7±5.1 years old) were enrolled in the FIT-AGEING study. Cardiorespiratory fitness was determined by a maximum treadmill test using indirect calorimetry. Lower, upper, and core body muscular strength were assessed by an isokinetic strength test, by the handgrip strength test, and by several core strength endurance tests, respectively. All the exercise types induced similar increases on cardiorespiratory fitness (Δ VO2max≥11%, Δ maximal heart rate≥8%, and Δ total test duration ≥14%; all P≤0.034), as well as on muscular strength (Δ extension and flexion peak torque≥10%, Δ total hand grip ≥3%, Δ core strength endurance tests≥20%; all P≤0.050) compared with a control group. In conclusion, our results suggest that a 12-week structured exercise intervention improves physical fitness regardless of the training programme in sedentary middle-aged adults. Despite slightly greater improvements in some physical fitness variables, the changes observed in the WB-EMS group were not superior to the other exercise programmes.